Sikap Masyarakat Terhadap Pemilu Presiden 2024: Studi Kasus Desa Jebeng Kecamatan Slahung: Indonesia - Yusuf Vreda Adi Wardana; Yusuf Adam Hilman; Jusuf Harsono; Bambang Widyahseno (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2022)
Presidential election is a form of democracy that is implemented in Indonesia. In this case, the community responds with various perceptions. People's attitudes in responding to the presidential election that will be held in 2024 have various kinds. This study uses a qualitative descriptive method with interview techniques with informants, namely the people of Jembeng Village, Slahung District. The use of this method as a way to strengthen the data that will be obtained by researchers. And the use of the documentation method is to match the findings in the field with community responses. The results of this study are the people of Jebeng Village, Slahung District, know about the presidential election through billboards that are installed on the side of the road. The public also has knowledge about the 2024 presidential election and the chances of a candidate pair winning.